Simulation Studies of Gas-Solid in the Riser of a Circulating Fluidized Bed - Hussain, Ahmad; Ani, Farid Nasir; Darus, Amer Nordin; Mustafa, Azeman; Salema, Arshad A. (2005)
A numerical parametric study was performed on the influence of various riser exit geometries on the hydrodynamics of gas-solid two-phase flow in the riser of a Circulating Fluidized Bed (CFB). A Eulerian continuum formulation was applied to both phases. A two fluid framework has been used to simulate fully developed gas-solid flows in vertical riser. A two dimensional Computational Fluid Dynamics (CFD) model of gas-particle flow in the CFB has been investigated using the code FLUENT. The turbulence was modeled by a k-e turbulence model in the gas phase. The simulations were done using the geometrical configuration of a CFB test rig at the Universiti Teknologi Malaysia (UTM). The CFB riser column has 265 mm (width), 72 mm (depth) and 2.7 m height. The riser is made up of interchangeable Plexiglas columns. The computational model was used to simulate the riser over a wide range of operating and design parameters. In addition, several numerical experiments were carried out to understand the influence of riser end effects, particle size, gas solid velocity and solid volume fraction on the simulated flow characteristics. The CFD model with a k-e turbulence model for the gas phase and a fixed particle viscosity in the solids phase showed good mixing behaviour. These results were found to be useful in further development of modeling of gas solid flow in the riser.